Implications of urbanization, consumer awareness, and income trends on future food supplies in Senegal - Marivoet, Wim (International Food Policy Research Institute, 2024)
This research report aims to identify major food supply implications and potential entry points for a more efficient, nutritious, sustainable, and equitable transformation of Senegal’s food system. Inspecting key indicators from the FSD, Senegal’s food system is indeed failing to provide healthy diets to the population in an inclusive and sustainable manner. For example, total food supplies are estimated to be energy insufficient (below 2,500 kilocalories (kcal) per capita per day in 2013), lacking diversity (especially in terms of fruit and pulses, with supplies of only 53 and 15 grams (g) per capita per day in 2019, respectively), and potentially threatening soil biodiversity. Therefore, it is unsurprising to observe that 46 percent of the population in 2020 was unable to afford a healthy diet and 49 percent was moderately or severely food insecure. This is also reflected in the poor performance of dietary indicators for infants and children, as well as the high anemia prevalence in women.